Ð“ÐµÐ¼Ð¾Ð¿Ð¾ÐµÑ‚Ð¸Ñ‡Ð½Ñ– ÑÑ‚Ð¾Ð²Ð±ÑƒÑ€Ð¾Ð²Ñ– ÐºÐ»Ñ–Ñ‚Ð¸Ð½Ð¸ Ð² Ñ‚Ñ€Ð°Ð½ÑÐ¿Ð»Ð°Ð½Ñ‚Ð°Ñ†Ñ–Ñ— Ñƒ Ñ…Ð²Ð¾Ñ€Ð¸Ñ… Ð½Ð° Ð¾Ð½ÐºÐ¾Ð³ÐµÐ¼Ð°Ñ‚Ð¾Ð»Ð¾Ð³Ñ–Ñ‡Ð½Ñƒ Ð¿Ð°Ñ‚Ð¾Ð»Ð¾Ð³Ñ–ÑŽ - Misharina, Zh. A.; Balan, V. V.; Kryachok, I. A.; Minchenko, Zh. M.; Belyayeva, N. V.; Samson, Yu. M.; Chuyskiy, V. G.; Karamanesht, Ye. Ye.; Khomenko, V. I.; Bebeshko, V. G. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
The research performed demonstrated that the hemopoietic cells, derived from bone marrow (BM), peripheral and cord blood, were of a high proliferative potential and might be considered as the source for transplantation. The peripheral blood (PB) should be considered as the main source of stem cells for auto- and allotransplantation performance. The proposed methods for PB stem cells enrichment enable to obtain the number of stem cells with preserved functional activity, sufficient for hemopoietic stem cells transplantation. The usage of BM as a transplant is expedient only at insufficient collection of peripheral blood SCs. Cord blood is the most perspective source for further application as allo- and autotransplantats.